2008
DOI: 10.1167/8.14.12
|View full text |Cite
|
Sign up to set email alerts
|

Salient features in gaze-aligned recordings of human visual input during free exploration of natural environments

Abstract: During free exploration, humans adjust their gaze by combining body, head, and eye movements. Laboratory experiments on the stimulus features driving gaze, however, typically focus on eye-in-head movements, use potentially biased stimuli, and restrict the field of view. Our novel wearable eye-tracking system (EyeSeeCam) overcomes these limitations. We recorded gaze- and head-centered videos of the visual input of observers freely exploring real-world environments (4 indoor, 8 outdoor), yielding approximately 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 69 publications
3
47
0
Order By: Relevance
“…This focus on instruction was demonstrated by the longer durations of teacher gaze towards non-research regions in contrast to research regions of the classroom. As expected, participating teachers' gaze demonstrated that the complexity (Chisholm, Caird & Lockhart, 2008), difficulty (Rötting, 2001) and importance (Mackworth & Morandi, 1967;Schumann et al, 2008) of the non-research areas dramatically outweigh those of research areas in the classroom. We were not surprised that video research imposed minimal attentional distraction on teachers, given the pressured, sophisticated and unpredictable nature of classroom teaching (e.g., Berliner, 2001).…”
Section: Change In Teacher Reactivity Over Timesupporting
confidence: 58%
“…This focus on instruction was demonstrated by the longer durations of teacher gaze towards non-research regions in contrast to research regions of the classroom. As expected, participating teachers' gaze demonstrated that the complexity (Chisholm, Caird & Lockhart, 2008), difficulty (Rötting, 2001) and importance (Mackworth & Morandi, 1967;Schumann et al, 2008) of the non-research areas dramatically outweigh those of research areas in the classroom. We were not surprised that video research imposed minimal attentional distraction on teachers, given the pressured, sophisticated and unpredictable nature of classroom teaching (e.g., Berliner, 2001).…”
Section: Change In Teacher Reactivity Over Timesupporting
confidence: 58%
“…Gaze-centred and head-centred videos were recorded using the ''EyeSeeCam'' setup, which is described in detail elsewhere (Brandt, Glasauer, & Schneider, 2006;Schneider et al, 2005Schneider et al, , 2006Vockeroth, Bardins, Bartl, Dera, & Schneider, 2007), as is the recording procedure and the stimulus material (Schumann et al, 2008). In brief, an eyetracking system attached to swimming goggles controls a gaze-centred camera, while an identical camera (head camera) is fixed to the observer's forehead.…”
Section: Free Explorationmentioning
confidence: 99%
“…EyeÁhead-coordination analysis suggested a profound influence of nonsaccadic eye movements to gaze-centred stimulus statistics (Einhäuser et al, 2007;Einhäuser, Moeller, et al, 2009), and the spatial statistics of features at the centre of gaze transferred the concept of feature saliency from the laboratory to the real world Schumann et al, 2008). A direct comparison between free exploration and laboratory data with the same visual input has, however, yet to be performed.…”
mentioning
confidence: 99%
“…Natural shifts of attention to a large degree occur through movement, in particular via overt whole-body movements of gaze including eye-, head and body (Land and Hayhoe, 2001;Schumann et al, 2008;'t Hart et al, 2009). On the one hand, attention can move automatically and transiently between places in the world via exogenous reflexive stimulusdriven processes, presumably to direct the sense organs to highly salient aspects and potential danger (Posner, 1980;Prinzmetal et al, 2005).…”
Section: Attention Is Closely Linked To Movementmentioning
confidence: 99%